Agent for exam processing / Chong Foh Peng - Chong, Foh Peng (2001)
Exam Processing System is a necessity to every Institution of higher learning and universities, due to the amount of students taking exams every year, the blooming of information technology era and achieving the paperless environment goal. It has been implemented to handle student's records or more widely recognized as the Student Information System (SIS). However, based on the current system, it can only keep records and do very little with it, which requires the administrators more time to generate the summary manually. Agent for Exam Processing is proposed to overcome these shortcomings. The Agent for Exam Processing is an intelligent web application system designed to reduce the time spent on keying in the results, processing it, and come out with a detail summary. The main objective of this agent is to help lecturers, administrators and students to handle the compiled results in a more precise and professionally manner. Most of the required job will be done automatically using computer Intelligence, such as recognizing weak students and inform the lecturer, determining the number of credit hours allowed, coming out with result statistics and so on. In this way, students can get their results earlier and register the appropriate number of credit hours for the next semester. It saves the hassle of registering and later dropping some courses after knowing their GPA only allows them to take a certain amount of credit hours. With its user-friendliness, easy maintenance, and intelligence, the agent is able to provide a comprehensive Exam Processing system for the field of education. The Agent for Exam Processing os divided into three main sections, namely the Acess, Administrator, Lecturer and Student. Each of the section has its own modules, which handles different task and operations. Hence, it makes the agent more effective, efficient and reliable. For instance, lecturers could key in the student's test, quiz, assignment or exam records at any time and view the statistics instantly. All users (administrators, lecturers and students) will be authenticated with their own username and password. Besides that, students will be notified by email when their result is out. The Agent for Exam Processing is developed with a combination of web programming technologies namely Active Server Pages (ASP), VBScript, HTML. The entire platform of the agent requires Windows NT Server, Microsoft SQL Server, Microsoft Internet Information Server, Windows 95/98/NT/2000 Workstations and Microsoft Internet Explorer 4.0 or above. The Microsoft Visual InterDev and Notepad are selected as the development tools for this project.